Answer:
s = t⁴/108+6t+24
v = t³/27 + 6
Step-by-step explanation:
Given the equation of acceleration expressed as a = kt²
t is in seconds
To get the velocity, we will integrate the acceleration function
a = kt²
Integrate both sides
a = kt²
v = ∫kt² dt
v = k ∫t² dt
v = kt³/3 + C1..... *
s = ∫kt³/3 dt+ ∫C1 dt
s = kt⁴/12+C1t + C2
At t = 0, S= 24
24 = k(0)⁴/12 + C1(0)+ C2
24 = C2
s = kt⁴/12+C1t + 24
If at t = 6 seconds, s = 96m
Substitute;
96 = k6⁴/12+6C1+ 24 .... **
Also at t = 6, v = 18m/s
Substitute into *
v = kt³/3 + C1..
18 = k6³/3 + C1..... ***
Solve ** and *** simultaneously and get k and C1
96 = k6⁴/12+6C1+ 24
k6⁴/12+6C1+ = 72 × 1
k6³/3 + C1 = 18 × 6
---------------------------
k6⁴/12+6C1+ = 72
k6⁴/3 + 6C1 = 108
Subtract
[(6⁴k)-4(6⁴k)]/12 = 72-108
-3(6⁴k)/12 = -36
6⁴k/12 = 12
6⁴k = 144
k = 144/1296
k = 1/9
Substitute k = 1/6 into k6³/3 + C1 = 18 and get C1
1/6(216/3) + C1 = 18
12+ C1= 18
C1 = 18-12
C1 = 6
Write s in terms of t;
s = kt⁴/12+C1t + 24
s = 1/9t⁴/12+6t+24
s = t⁴/108 + 6t + 24
Write v in terms of t;
v = kt³/3 + C1
v = 1/9(t³/3)+6
v = t³/27 + 6